Dentists' perceptions and usability testing toward the implementation of the ISAC, a comprehensive oral cancer intervention in dental practices: a qualitative study in Jazan region, Saudi Arabia - Ibtisam Moafa; Ciska Hoving; Bart van den Borne; Mohammed Jafer (BMC, 2022)
Abstract Objective We aimed to explore dentists' perceptions toward the implementation of a comprehensive intervention (ISAC) for the early detection and prevention of oral cancer in a dental clinic. Methods The ISAC intervention was presented to ten purposefully sampled dentists in Jazan Dental School (JDS). Participating dental interns were asked to practice the ISAC intervention whilst thinking aloud. A semi-structured interview technique was used to allow free expression of participants' perceptions related to the ISAC intervention and to control the flow of topics. Fleuren's framework theory informed the analysis. The interviews were transcribed verbatim and analyzed using the deductive-inductive framework analysis. Results Practicing the ISAC intervention was perceived to enhance the early detection and prevention of oral cancer. Serving community needs and engaging community groups were perceived to be related to a high relevance and compatibility of the ISAC intervention. Being a comprehensive intervention with well-defined objectives and being built on relevant data from the participants' community and having dentists as a target group were the perceived relative advantages of the ISAC intervention compared to other programs. A supportive environment, gender-concordance, use of regional trainers, standard examination form and collaboration with other sectors were perceived to be the facilitators. Competition with clinical time, use of different examination forms and low organizational leader interests were perceived as impeding factors against effective implementation in a real-world context. Reward, easy to practice, feeling confidence and satisfaction, advertisement as well as use of a role model approach were perceived to be motivating factors. Conclusions Integrating data from representers of different participant groups during intervention conceptualization and development are critical for the intervention compatibility and acceptability. The study findings showed the opportunities of intertwining the intrinsic motivators of satisfaction and altruism existing in the target group and the extrinsic motivator of official diagnostic skill, certification that may boost and sustain the behavior change. Intervention features that influence perceived relevance, compatibility, relative advantage and motivation may be of great importance for intervention practice.